Zoo Jana Brzechwy a uczenie dzieci języka polskiego jako odziedziczonego - Wacławek, Maria (Postscriptum Polonistyczne, 2020)
Literary texts presented to children during Polish as a foreign language classes must be suitable for the purposes of the lesson as well as the learners’ language competence, interests and intellectual and cognitive abilities. Brzechwa’s poems about animals are of great educational and didactic value. The animals represent different features reflected in certain idiomatic expressions that create the linguistic image of the world. Brzechwa’s poems can be used for various linguistic exercises; they can also inspire children to create their own texts.